INCIDENCE AND ETIOLOGY OF VENTILATOR-ASSOCIATED PNEUMONIA IN PEDIATRIC INTENSIVE CARE UNIT AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: To find out the incidence and etiology of ventilator-associated pneumonia (VAP)in pediatric intensive care unit.Subjects and methods: Descriptive study of 173 patients requiring mechanical ventilator ≥ 48hours at Nghe An Obstetrics and Pediatrics Hospital from August 2020 to July 2022.Results: 47 patients suffered ventilator-associated pneumonia with 51 episodes met the criteriafor VAP. The incidence rate reached up to 27,1% and 30,9/1000 mechanical ventilator days. Themost frequently isolated mico-organisms were Acinetobacter baumannii (29,7%), followed byKlebsiella pneumoniae (22,2%) and Pseudomonas aeruginosa (18,5%). By compared with nonVAP group, VAPs were closely related to longer ventilator, intensive care unit stay time andhospitalization time.Conclusions: The incidence of VAP in this study was relatively high, strict supervision ofinfection control protocols are crucial.
Keywords: Ventilator-associated pneumonia (VAP), incidence, micro-organism etiology, outcome.